2018
DOI: 10.48550/arxiv.1811.10721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-dependent injection strategies and interfacial stability in multi-layer Hele-Shaw and porous media flows

Abstract: We study the stability of multi-layer radial flows in porous media within the Hele-Shaw model. We perform a linear stability analysis for radial flows consisting of an arbitrary number of fluid layers with interfaces separating fluids of constant viscosity and with positive viscosity jump at each interface in the direction of flow. Several different time-dependent injection strategies are analyzed including the maximal injection rate that maintains a stable flow. We find numerically that flows with more fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The constant viscosity case is given by the solid (black) line and the viscosity of the middle layer fluid is µ = 6. The stability of three-layer constant viscosity flows has been studied extensively by Gin & Daripa (2015, 2018. Note that there is a maximum growth rate and that short waves are stable due to interfacial tension.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The constant viscosity case is given by the solid (black) line and the viscosity of the middle layer fluid is µ = 6. The stability of three-layer constant viscosity flows has been studied extensively by Gin & Daripa (2015, 2018. Note that there is a maximum growth rate and that short waves are stable due to interfacial tension.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…We now turn to three-layer flows in which the fluid in the middle layer also has constant viscosity, µ 1 . This situation has been investigated by Beeson-Jones & Woods (2015) and Gin & Daripa (2018), and it has been found that the magnitudes of interfacial disturbances A n (t) and B n (t) are governed by the following system of ODE's…”
Section: Constant Viscosity Fluidsmentioning
confidence: 99%
See 2 more Smart Citations